The role of Morrey spaces in the study of Navier–Stokes and Euler equations - Lemarié–Rieusset, P. G. (Eurasian Mathematical Journal, 2012)
In this survey, we will pay a few words on the solution of the Cauchy problem for the 3D Navier-Stokes or Euler equations (with a focus on real harmonic analysis